Implementasi Daily Literacy, Story Telling, dan Pojok Baca Pada Minat Baca Siswa SMP IT Nurul Quran Al Aziziyah - Hendriawan, M. Zulia; Alfiana, Khairi; Nurnabilah, Nurnabilah; Ramadhan, Rifki Awallul; Farhan, M. Zainul; Lu'luilmaknun, Ulfa (Rengganis Jurnal Pengabdian Masyarakat, 2025)
Daily Literacy, Story Telling, and Reading Corner are programs of the Kampus Mengajar (KM) 8 team at SMP IT Nurul Quran Al Aziziyah. The purpose of implementing Daily Literacy, Story Telling, and Reading Corner is to describe the role of language literacy in increasing reading interest in students of SMP IT Nurul Quran Al Aziziyah. The Implementation Method for this activity are the preparation, implementation, and evaluation stages. The preparation stage starts on September 10-13, 2024. Implementation for Daily Literacy, Story Telling, and Reading Corner has been carried out in September-November 2024. Through interviews with the principal, teachers and students as well as observations and documentation were carried out to determine the literacy level of students of SMP IT Nurul Quran Al Azziyah as material for evaluating activities. Based on the data collected, it is then described and analyzed. It can be concluded that 1) literacy activities at SMP IT Nurul Quran Al Azziyah play a role in motivating students to like reading and writing activities, 2) the obstacles of the school in increasing the interest in reading and writing of upper-class students through literacy activities are discipline, student habits, interests, and methods applied by teachers, and 3) the school's efforts to increase the interest in reading and writing of upper-class students through literacy activities are that the school always provides socialization regarding literacy activities, introduces the importance of fostering interest and holds competitions as a forum for students to actively participate.